From ecosystem valuation to transformational governance: Interdisciplinary pathways for sustainable coastal and marine futures - Yudi Wahyudin (Aurelia Journal, 2026)
Coastal and marine ecosystems provide critical economic, ecological, and social benefits, yet they continue to experience accelerated degradation driven by sectoral governance, weak enforcement, and persistent environmental conflicts. Over the past decades, ecosystem service valuation has generated substantial evidence on the economic significance of coral reefs, seagrass, mangroves, and fisheries. However, this evidence has rarely been translated into effective policy action, legal enforcement, or preventive governance mechanisms. This paper addresses this gap by examining how ecosystem valuation can evolve from a descriptive economic tool into a foundational element of transformational coastal and marine governance.  Using an interdisciplinary policy-oriented approach, this study synthesizes advances in ecosystem valuation, social-ecological systems (SES) analysis, marine audit practices, fisheries bioeconomics beyond maximum sustainable yield (MSY), and ethical governance instruments. Drawing on empirical and policy-relevant experiences from Indonesian coastal and marine contexts, including ecosystem damage claims, zoning violations, fisheries overexploitation, and valuation-based legal processes, the paper demonstrates both the achievements and limitations of valuation in influencing governance outcomes.  The results highlight that valuation becomes policy-relevant only when embedded within an integrated governance architecture. Marine audit is identified as a key institutional innovation that operationalizes valuation as an early detection, compliance monitoring, and conflict prevention mechanism. Furthermore, extending fisheries management toward maximum economic yield (MEY), welfare-oriented indicators, and ecosystem approach to fisheries management (EAFM) strengthens the linkage between economic efficiency, social equity, and ecological sustainability. The incorporation of ethical and social finance instruments, such as sharia-based fisheries management, zakat-infaq-shadaqah (ZIS), and waqf-based conservation models, provides long-term financing mechanisms and normative legitimacy for sustainable resource governance.  This paper proposes a transformational governance framework built on four integrated pillars: ecosystem valuation, SES-based system understanding, marine audit and legal enforcement, and ethical finance and social innovation. Policy implications emphasize the need for mandatory valuation in marine spatial planning and licensing, institutionalized marine audit systems, valuation-based legal standards, and preventive governance strategies. The framework offers a practical pathway for bridging science and policy, enhancing environmental justice, and achieving sustainable coastal and marine futures in Indonesia and comparable coastal nations.